PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN MASYARAKAT DALAM PEMBUATAN PASPOR DI KANTOR IMIGRASI KELAS I TEMPAT PEMERIKSAAN IMIGRASI BANDAR LAMPUNG - Adrian Tawai; Rola Pola Anto; Haerul Ikrar Rusli (Universitas Bandar Lampung (UBL), 2020)
The lack of good quality of service at the Class I Immigration Office at the Bandar Lampung Immigration Checkpoint can lead to a crisis of trust in the community, which can be in the form of people still feeling convoluted, non-transparent, less informative, less accommodating and inconsistent service procedures and mechanisms so that they do not guarantee legal certainty, time and cost. So that this results in the emergence of other phenomena such as the high costs that must be incurred by the community as users of public services provided by the government. For this reason, bureaucratic reform in the field of public services must be a top priority for the government.The problem in this study can be formulated, namely